Sodium reduction by hyposodic salt on quality and chemical composition of hamburgers - Ramos, Tatiane Rogelio; Pelaes Vital, Ana Carolina; Mottin, Camila; Torrecilhas, Juliana Akamine [UNESP]; Valero, Maribel Velandia; Guerrero, Ana; Barbosa Carvalho Kempinski, Emilia Maria; Prado, Ivanor Nunes do (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
This work evaluated the effect of NaCl reduction on the quality and sensorial attributes of hamburgers. Three treatments were tested: control (CON), 100% NaCl; reduction of 25% NaCl (T25), and one with 50% NaCl (T50). The pH, color, lipid oxidation, cooking losses, and texture were analyzed during 120 days of freezing storage. Chemical composition and sensory analyses were performed. The chemical composition was similar for all treatments. The pH value remained within acceptable limits throughout storage. The color, lipid oxidation, cooking losses, and texture were not influenced by the sodium replacement and freezing storage. Sensorial acceptability was also not influenced by sodium reduction. Thus, the results indicated that up to 50% replacement of NaCl by KCl could be carried out in hamburger production without altering the quality and sensorial acceptability.
Keywords: color; chemical composition; lipid oxidation; potassium chloride; sensorial evaluation